Quantum Micro–Nano Devices Fabricated in Diamond by Femtosecond Laser and Ion Irradiation (Adv. Quantum Technol. 5‐6/2019). Issue 5 (12th June 2019) - Eaton, Shane M.; Hadden, John P.; Bharadwaj, Vibhav; Forneris, Jacopo; Picollo, Federico; Bosia, Federico; Sotillo, Belen; Giakoumaki, Argyro N.; Jedrkiewicz, Ottavia; Chiappini, Andrea; Ferrari, Maurizio; Osellame, Roberto; et al.
Abstract : Femtosecond laser writing and ion irradiation have been demonstrated as powerful fabrication tools for integrated quantum photonics in diamond in article no.1900006 . The figure depicts femtosecond laser inscription and ion beam irradiation in diamond, which can be applied separately, or potentially together, to accurately form nitrogen vacancy (NV) center defects within synthetic diamond. The nitrogen (shown as yellow sphere)–vacancy (shown as light pink sphere) color center defect in the tetrahedral lattice of carbons (shown as black spheres) has emerged as a suitable candidate for a qubit (represented by the Bloch sphere above the diamond) for quantum information and field sensing applications. In addition, the article highlights the latest results on laser and ion beam irradiation fabrication of integrated photonic and microfluidic components in diamond for interfacing with NV centers.